Cheese problems solved - McSweeney, P. L. H. (Woodhead Publishing in food science, technology, and nutrition., 2007)
Cheese is a unique food product which requires a significant amount of scientific knowledge to be produced successfully. However, due to the many, complex and interrelated changes which occur during cheese manufacture and ripening, it is still not possible to guarantee the production of premium quality cheese. Written by an international team of renowned contributors, Cheese problems solved provides responses to over 200 of the most frequently asked questions about cheese and the cheese-making process, in a unique and practical question-and-answer format. Opening chapters concentrate on queries regarding the preparation of cheese milk, the conversion of milk to curd, the ripening process, pathogens, cheese analysis and nutritional aspects of cheese amongst other issues. The latter half of the book discusses particular types of cheeses such as Cheddar, Grana-type cheeses, Mozzarella, Dutch-type, Swiss and Blue cheeses, to name but a few. Edited by a leading expert and with contributions from specialists within the field, Cheese problems solved is an essential reference and problem solving manual for professionals and trainees in the cheese industry. Provides responses to over 200 of the most frequently asked questions about cheese and the cheese-making processAn essential reference and problem solving manual for professionals and trainees in the cheese industryBenefit from the knowledge of leading specialists in the field.